Influence of Xanthan Gum-Based Soil Conditioners on the Geotechnical Properties of Soils - Barbara Fortuna; Janko Logar; Alessandro Sorze; Francesco Valentini; Jasna Smolar (Applied Sciences, 2024)
The impact of climate change has become increasingly severe in forests, where droughts and strong winds on the one hand and extreme rainfall events on the other hand can damage forest ecosystems. To mitigate the effects of drought and enhance soil water retention capacity, three types of soil conditioners (SCs), labeled SC_R, SC_CG, and SC_ZZC, were developed as part of the European project ONEforest. All the conditioners are based on Xanthan gum and have different types and amounts of fillers with diverse cellulose fiber lengths. These can offer the potential to optimize the SC characteristics, e.g., water absorption, water retention, and mechanical stability. This paper focuses on the influence of fillers in the SCs on the geotechnical properties of forest soils from Ljubelj in the Alpine part of Slovenia (S1), Catalonia, northeastern Spain (S2), and Heldburg, Germany (S3). The results show an increase of 53% to 100% in the water absorption of treated soil. A less favorable impact of the SCs was found on the drained shear strength and the compressibility. The drained shear strength of untreated forest soils in a saturated state was S1 c′ = 4.4 kPa, φ′ = 33.5°; S2 c′ = 1.4 kPa, φ′ = 30.0°; and S3 c′ = 12 kPa, φ′ = 28.0°. The addition of SCs results in a reduction in the drained shear strength of saturated mixtures. The reduction depends on the dosage of added SC—whether it is a low (L) or a high (H) dosage. For instance, when the soil S1 was treated with a low dosage of the soil conditioner SC_R, it demonstrated a cohesion (c′) of 11 kPa and a friction angle (φ′) of 27.0°. However, increasing the dosage of the SC_R led to a decrease in both the cohesion and the friction angle for the same soil (c′ = 7.7 kPa, φ′ = 25.0°). Additionally, the type of soil conditioner also impacts the drained shear strength. Among the mixtures with a high dosage of the SC_R, SC_CG, or SC_ZZC, those containing the SC_CG with the longest fibers stand out, demonstrating the highest friction angle. Therefore, longer fibers can be a promising component of the SCs to reduce the negative influence of XG on the mechanical properties of treated soils.